2020
DOI: 10.2147/opto.s250813
|View full text |Cite
|
Sign up to set email alerts
|

<p>Visual Acuity Improvement in Adult Anisometropic Amblyopes After Active Vision Therapy</p>

Abstract: The aim of this study is to evaluate the effect of active vision therapy in adults with anisometropic amblyopia. Methods: In this study, 20 adults with anisometropic amblyopia aged from 17-35 years old were treated for five sessions (one session per week) with vision therapy techniques which include accommodative rock, vergence rock, and saccadic training. Moreover, computerized vision therapy was performed by Optosys ® software. Also, patients had been given a daily program for home training, including accomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The other major concern participants had was concerning the lack of treatment or cure for their eye condition. Treatment for adults with anisometropic amblyopia is gaining momentum based on recent evidence of positive outcomes 34–36 ; however, it is not commonly offered in routine clinical practice. As such, it is surprising that the old myth that ‘amblyopia can only be treated during the critical period’ still prevails among eye care practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…The other major concern participants had was concerning the lack of treatment or cure for their eye condition. Treatment for adults with anisometropic amblyopia is gaining momentum based on recent evidence of positive outcomes 34–36 ; however, it is not commonly offered in routine clinical practice. As such, it is surprising that the old myth that ‘amblyopia can only be treated during the critical period’ still prevails among eye care practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study with previously untreated adults (17–35 years old) with anisometropic amblyopia performing patching (2 hours/day for 5 weeks) with near visual activities found an increase in visual acuity (0.23 logMAR). 23 The three subjects with anisometropia in the current study also displayed an increase in acuity of 0.23 logMAR (t 2 = 2.043, p = 0.18), whereas the six subjects with combined mechanism amblyopia only had an acuity increase of 0.13 logMAR (t 5 = 2.874, p = 0.04). Most subjects in the present study had a history of previous patching (7/9) or strabismus surgery (1/9) thus previous treatment is not a limiting factor for acuity improvement.…”
Section: Discussionmentioning
confidence: 42%
“…However, other large multi-center studies have suggested that binocular perceptual learning techniques are not any more effective than traditional patching or non-binocular therapies in both children and adults with amblyopia. [20][21][22] A recent article suggests that standard patching for 2 hours per day combined with near visual activities results in an improvement in acuity (average acuity improved from 0.37 ± 0.04 to 0.14 ± 0.03 logMAR) for previously untreated adults (age [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] with anisometropic amblyopia. 23 However, another study suggests that previously untreated adults with amblyopia may only obtain a small improvement in acuity with patching (0.05 logMAR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients should be kept under regular follow-up and monitored for complication development. Appropriate refractive error correction should be given and, if required, amblyopia correction therapy should be considered in children and adults [ 11 ]. Surgical management should be reserved for cases developing complications.…”
Section: Discussionmentioning
confidence: 99%